A case-control study of sporadic infection with O157 and non-O157 verocytotoxin-producing Escherichia coli. - Piérard, D. (Cambridge University Press, 1999)
Potential risk factors for sporadic verocytotoxin-producing Escherichia coli (VTEC) infection in Belgium were investigated in a matched case-control study. Thirty-seven cases, 8 infected with O157 VTEC strains (all eaeA-positive), 29 with non-O157 VTEC strains (13 eaeA-positive and 16 eaeA-negative) and 69 matched controls were interviewed. In a conditional logistic regression analysis, consumption of fish appeared to be a risk factor for infection (adjusted odds ratio (OR) 3.25, P = 0.04). Contact with dogs (OR 0.27, P = 0.04) and consumption of shellfish (OR 0.19, P = 0.05) showed a negative association, corresponding to a decrease in risk. These findings might be explained if low level environmental exposure to VTEC induces protective immunity. Eating raw meat, a frequent habit in Belgium, or hamburgers, or eating in a fast-food restaurant was not more frequently reported by cases than controls. The exposures causing sporadic infections with VTEC, in particular non-O157 strains, may be very different from those which led to outbreaks, and may account for more cases overall.